Realism and the American dramatic tradition - Demastes, William W. (University of Alabama Press, 1996)
This work reconsiders realism on the American stage by addressing the great variety and richness of the plays that form the American theatre canon. It traces the development of American dramatic realism from James A. Herne, the "American Ibsen" to contemporary dramatists such as Sam Shepard.